(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
The paper represents an excursus in methods in teaching English, presented methods of teaching English in some foreign countries. Their advantages and disadvantages, the most effective methods of their adaptation to the specifics of the uzbek model of education are given.